Балалар ҳәм жас өспиримлер темасындағы материаллардыӊ тәсиршеӊлиги ҳәм нәтийжелилиги (SCIENCE and SOCIETY, 2022)
This article discusses the role of children’s education and the media in the life of society in the context of globalization, in particular, the role and importance of children’s journalism, as well as the skills of journalists working in the field of children’s